JIG & FIXTURE DESIGN FOR ROUGHNESS TESTER SJ-210 - Nanda Rahmaniar Siswanda; Sufiyanto Sufiyanto; Sudjatmiko Sudjatmiko (University of Merdeka Malang, 2019)
The rapid development of the industry gave rise to better technological innovations to develop the quality capacity of a production. Jig fixture is a production tool used in the manufacturing process, so that accurate part duplication is produced. Jigs fixture specifically designed to facilitate the setup of materia; which ensures uniformity in the shape and size of products in large quantities (mass products), and commemorate the time of production [2-4]. Jig fixture functions to hold and direct the workpiece, so that the manufacturing process is more efficient and product quality can be maintained as specified quality. Rong and Zhu (1999) in Ahmad Rizki (2003) state that an object consists of several surface surfaces. In the use of a fixture, the placement process (locating) is the process of placing multiple surfaces of a workpiece until it touches the locator, which is then followed by the clamping process of the workpiece that comes in contact with the locator called a locating surface. In a workpiece there are 6 degrees of freedom (degree of freedom) of movement, ie linear motion in the direction or counterclockwise with the X, Y, Z axis and rotational movements towards the X, Y, and Z axis in a clockwise or counterclockwise direction.